Rancang Bangun Akun Instagram sebagai Sarana Informasi Perpustakaan Wacana Teknologi SMKN 1 Majalengka - Yunus Winoto; Fitri Perdana (Institut Agama Islam Negeri (IAIN) Curup, 2023)
The Technology Discourse Library is a library managed by SMKN 1 Majalengka. The library has a significant development since 2020, yet this development has not done simultaneously with a proper media for sharing information, this causing the libary to be less well known by school users. Therefore, the school need a media that could be used for sharing information to help the library to be less unknown. The research method use in this paper is Action Research model by Burns with five steps on the first cycle and four steps on the continuation cycle. The data in this paper retrieved through interview, observation, and documentation. This research went through two cycles with result in the form of an Instagram account with @perpus.stemanika as username and managed by Technology Discourse Library SMKN 1 Majalengka’s staff. This Instagram account can be used as media for sharing information by Technology Discourse Library SMKN 1 Majalengka